2022
DOI: 10.3390/rs14143273
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Electrostatic–Atomic Accelerometer for Future Space Gravity Missions

Abstract: Long-term observation of Earth’s temporal gravity field with enhanced temporal and spatial resolution is a major objective for future satellite gravity missions. Improving the performance of the accelerometers present in such missions is one of the main paths to explore. In this context, we propose to study an original concept of a hybrid accelerometer associating a state-of-the-art electrostatic accelerometer (EA) and a promising quantum sensor based on cold atom interferometry. To assess the performance pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 92 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Such systems enable the study of weak trapping potentials and observing atomic ensembles after long evolution times. This, in turn, may allow for very low temperatures [25] and large scale factors in atom interferometry [26][27][28][29]. Space-borne atom interferometers were proposed for testing the UFF [30,31], Earth observation [32][33][34], dark matter and dark energy search, and cosmology [35] has been proposed.…”
Section: Cold and Condensed Atom Experiments In Microgravitymentioning
confidence: 99%
“…Such systems enable the study of weak trapping potentials and observing atomic ensembles after long evolution times. This, in turn, may allow for very low temperatures [25] and large scale factors in atom interferometry [26][27][28][29]. Space-borne atom interferometers were proposed for testing the UFF [30,31], Earth observation [32][33][34], dark matter and dark energy search, and cosmology [35] has been proposed.…”
Section: Cold and Condensed Atom Experiments In Microgravitymentioning
confidence: 99%
“…As expected, the Coriolis acceleration due to Ω y vanishes for Ω M = −Ω y . Besides, a term (11) corresponding to the motion of the mirror in the satellite appears in the phase expression. The centrifugal acceleration due to Nadir rotation around y axis is compensated only when this term is equal to x 0 Ω 2 y , which requires Ω M = Ω I = −Ω y , but also x M = 0.…”
Section: Effect Of a Rotation Compensationmentioning
confidence: 99%
“…Their sensitivity and accuracy are expected to increase dramatically in microgravity, where the interrogation time is no longer limited by the size of the instrument 2,3 . This triggered a recent interest in developing this technology for space [4][5][6] with potential applications in geodesy [7][8][9][10][11] , fundamental physics 12,13 , navigation and gravitational wave observation 14,15 . Opening the way to those developments, the CARIOQA Pathfinder Mission 16 aims at realizing the first quantum accelerometer on a satellite.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that such technology could be implemented on moving vehicles like spring gravimeters or forced balanced accelerometers (Bidel et al., 2018, 2020; Huang et al., 2022). Atom interferometry technology is finally also studied for the next generation of sensor for space gravimetry (Lévèque et al., 2021; Reguzzoni et al., 2021; Trimeche et al., 2019; Zahzam et al., 2022).…”
Section: Introductionmentioning
confidence: 99%